l Factor x^3-27y^9
Factor x3 - 27y9

Note the following cube root calculations

The cube root of the first term x3 = x ← This is {a}
The cube root of the second term 27y9 = 3y3 ← This is {b}

Since both cube roots are integer constants and powers, x3 - 27y9 is in the Difference of cubes format

The formula for factoring the Difference of cubes is as follows:

a3 - b3 = (a - b)(a2 + ab + b2)

Calculate ab

ab = (x)(3y3)
ab = (1 x 3)xy3
ab = 3xy3

Calculate the square of the a term:

The square of the a term = (x)2 = x(1 x 2)
The square of the a term = (x)2 = x2

Calculate the square of the b term:

The square of the b term = (3y3)2 = 32y(3 x 2)
The square of the b term = (3y3)2 = 9y6

Our factored expression using the Difference of cubes formula becomes:

(x - 3y3)(x2 + 3xy3 + 9y6)

Our factored out term becomes:



(x - 3y3)(x2 + 3xy3 + 9y6)